2012
DOI: 10.1159/000341502
|View full text |Cite
|
Sign up to set email alerts
|

A Short Introduction to Cytogenetic Studies in Mammals with Reference to the Present Volume

Abstract: Genome diversity has long been studied from the comparative cytogenetic perspective. Early workers documented differences between species in diploid chromosome number and fundamental number. Banding methods allowed more detailed descriptions of between-species rearrangements and classes of differentially staining chromosome material. The infusion of molecular methods into cytogenetics provided a third revolution, which is still not exhausted. Chromosome painting has provided a global view of the translocation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 143 publications
(72 reference statements)
0
22
0
3
Order By: Relevance
“…However, in the study of mammal chromosome evolution, most effort has been placed into determining how the genomes of the karyotypically diverse eutherian mammals have changed since their radiation approximately105 MYA. This is because comparisons with the other two mammalian lineages were impossible using cross-species chromosome painting (Graphodatsky et al 2012). As a consequence, most studies have focused on reconstructing the eutherian or boreoeutherian ancestral karyotype, rather than on that of the ancestor to all mammals.…”
Section: Mammalian Ancestral Karyotype Reconstructionsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in the study of mammal chromosome evolution, most effort has been placed into determining how the genomes of the karyotypically diverse eutherian mammals have changed since their radiation approximately105 MYA. This is because comparisons with the other two mammalian lineages were impossible using cross-species chromosome painting (Graphodatsky et al 2012). As a consequence, most studies have focused on reconstructing the eutherian or boreoeutherian ancestral karyotype, rather than on that of the ancestor to all mammals.…”
Section: Mammalian Ancestral Karyotype Reconstructionsmentioning
confidence: 99%
“…Such comparisons have shown that some of the associated segments revealed by chromosome painting amongst eutherian species represent an ancestral organization present in marsupials and even in chicken and the green anole. These associations include the association of segments from human chromosomes 4/8, 12/22, 14/15 and 16/19 (Graphodatsky et al 2012). The initial attempts made to reconstruct ancestral karyotypes purely from genome sequence comparisons for just a few eutherian species and using chicken as an outgroup, resulted in ‘mammalian’ ancestral karyotypes consisting of 2 n  = 42 (Bourque et al 2005; International Chicken Genome Sequencing C 2004).…”
Section: Mammalian Ancestral Karyotype Reconstructionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Those will contribute to clarify unresolved taxonomic problems in genets, allow reconstructing the chromosomal phylogeny of Genetta , and enable to assess some of the findings and hypotheses in this study. Further surveys should combine comparative chromosome painting with whole-genome sequencing, which permits more refined genome comparisons [Graphodatsky et al, 2012;Le Scouarnec and Gribble, 2012;Warren et al, 2015].…”
mentioning
confidence: 99%
“…Linking cytogenetic to genetic data was greatly enhanced after cytogenetics became a molecular science, allowing looking for the 'signature' of evolutionary processes in the 'chromosomics' era sensu Claussen [2005]. This role was reaffirmed with the culmination of genetic-based approaches and next generation sequencing technologies [Speicher and Carter, 2005;Dobigny and Yang, 2008;Graphodatsky et al, 2012]. Fish biologists, however, have seldom engaged in multidimensional studies including cytogenetic examination to address similar questions [e.g.…”
mentioning
confidence: 99%